2001
DOI: 10.1111/j.1745-9125.2001.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Practices of Gender: How Gender Relates to Delinquency in the Everyday Lives of High‐risk Youths*

Abstract: Conceptualizing gender as social practices and using those practices as the unit of analysis, I reanalyzed data from a study on gender and delinquency. The analysis disclosed six social practices that intertwined with delinquent activities, constraining female delinquency while enabling and rewarding male delinquency. Only a few differences emerged among three ethnic groups. This analysis suggests that the salient dimensions of gender as a correlate of delinquency include male dominance, differences in routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 25 publications
3
64
0
4
Order By: Relevance
“…One study found that adolescent girls, both delinquent and nondelinquent, report less use of influence by their peer group than adolescent boys (Giordano et al, 1986). Boys' antisocial acts, including physical aggression, are mostly directed against strangers, and are typically committed in a larger peer group format; in contrast, girls' aggression occurs most often between her and a family member (Pepler & Craig, 1999), and antisocial acts are committed in same sex pairs (Bottcher, 2001;Chamberlain & Reid, 1998). Further, mixed-sex peer groups probably influence females' willingness to engage in antisocial behavior, even if these acts are committed in sex-specific format.…”
Section: Peer Group Influencementioning
confidence: 93%
“…One study found that adolescent girls, both delinquent and nondelinquent, report less use of influence by their peer group than adolescent boys (Giordano et al, 1986). Boys' antisocial acts, including physical aggression, are mostly directed against strangers, and are typically committed in a larger peer group format; in contrast, girls' aggression occurs most often between her and a family member (Pepler & Craig, 1999), and antisocial acts are committed in same sex pairs (Bottcher, 2001;Chamberlain & Reid, 1998). Further, mixed-sex peer groups probably influence females' willingness to engage in antisocial behavior, even if these acts are committed in sex-specific format.…”
Section: Peer Group Influencementioning
confidence: 93%
“…There are slight differences in the masculine values attributed to street criminals by researchers, and there is ongoing discussion of regional and temporal variation in offenders' constructions of self (Bottcher 2001;Collier 1998;Winlow 2001). However, descriptions of street offenders' lifestyles and broad ideals are largely the same, and most everyone seems to agree that crime is especially likely to occur in situations that impugn or threaten character constructions based on claims of dangerousness, criminal know-how, or criminal capability (Athens 1997;Katz 1988;Messerschmidt 2000;Shover 1996, 107).…”
Section: Situational Accountability and Masculinitymentioning
confidence: 99%
“…Com efeito, a literatura sugere a existência de pressões sociais para que rapazes e raparigas se comportem de forma diferente, em função de estereótipos de género, o que significa que nos primeiros é mais encorajado o tipo de comportamentos que podem configurar a base para uma conduta delinquente, ocorrendo o contrário no caso das raparigas (e.g., Bottcher, 2001). No entanto, é plausível que quando se investigam raparigas que já se caracterizam por uma conduta delinquente, a disposição para essa conduta esteja nelas presente e, eventualmente, até de uma forma mais vincada, uma vez que têm de ultrapassar estereótipos sobre papéis e comportamentos sociais que no caso delas estão mais distantes de condutas antissociais do que no caso deles.…”
Section: Discussão E Conclusãounclassified
“…Os participantes do sexo masculino reportaram uma diversidade significativamente maior de atos delinquentes e o número desses atos é quase cinco vezes superior ao do sexo feminino. Por conseguinte, ainda que os rapazes investigados não se tenham distinguido das raparigas em termos de traços de personalidade antissocial, nem de disposição delinquente, são bem patentes as discrepâncias quanto a características criminológicas, como a frequência e versatilidade de comportamentos delitivos, na linha dos achados reportados na literatura (e.g., Bottcher, 2001;Holsinger, 1999;Moffitt et al, 2001). De notar que certos investigadores (Muñoz & Frick, 2007) avançam com a hipótese de a elevada frequência delitiva nos rapazes estar associada a traços de…”
Section: Discussão E Conclusãounclassified
See 1 more Smart Citation